The Repentance of the Ahmadiah Sect after the Emergence of the West Javanese Governor’s Regulation: A Case Study in Bogor (توبة جماعة الأحمدية بعد إصدار قرار رئيس الدائرة جاوى الغربية: دراسة واقعية في منطقة بوغور) - Ahmad Mukri Aji (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstrak: Pertaubatan Jamaah Ahmadiyah Pasca Terbitnya Peraturan Gubernur Jawa Barat: Studi Kasus di Wilayah Bogor. Gerakan Ahmadiyah telah menyebar ke setiap penjuru Negeri dengan membawa misi kesesatan yang merusak. Beragam fatwa bermunculan guna melarang gerakan ini, bahkan mengkafirkannya. Seperti larangan dari Lembaga Pengembangan Syariah di Dunia Islam, Lembaga Fiqhiyyah Râbithah al-‘Alam al-Islâmî, Lembaga Fikih Islam Organisasi Konferensi Islam, dan perhimpunan ulama-ulama di Kerajaan Arab Saudi, serta fatwa-fatwa ulama Mesir, Syiria, Maroko, India, Indonesia, dan sebagainya. Terakhir, adanya Keputusan Gubernur Provinsi Jawa Barat melarang gerakan ini. Keputusan ini membawa pengaruh, terlihat dengan bertaubatnya beberapa anggota Ahmadiyah. Adapun alasan mereka adalah kembali ke agama Islam yang benar.Kata Kunci: Ahmadiyah, paham sesat, fatwa ulama, Peraturan Gubernur Jawa Barat, pertaubatan AhmadiyahAbstract: The Repentance of  the Ahmadiah Sect after the Emergence of  the West Javanese  Governor’s Regulation: A Case Study in Bogor. The movement of the Ahmadiah has spread all over the country, carrying a misguided mission that causes harm. Various Islamic verdicts (Fatwa) have been promulgated to ban this movement, moreover, some of these verdicts have outcast the movement as infidel. Like the prohibitions from the Institution of Shariah Development in the Islamic World, Institution of the Fiqhiyyah Râbithah al-‘Alam, al-Islâmî, Institution of Islamic Tought of the Islamic Conference Organization, the Association of Islamic Scholars of  the Saudi Arabia as well as verdicts of Islamic scholars from Egypt, Syria, Maroko, India, Indonesia and etc. Lastly, there is the West Javanese Governor’s decision prohibiting this movement. This decision carries influence, seen by the repentance of some of sect members, returning them to their true  Islamic religion.Keywords: Ahmadiyah, astray sect, Islamic verdict, West Java Governor Regulation, Ahmadiah repentanceDOI: 10.15408/ajis.v12i1.988